Changing views on child mortality and economic sanctions in Iraq: a history of lies, damned lies and statistics. Issue 2 (24th July 2017) - Dyson, Tim; Cetorelli, Valeria
Abstract : In August 1990, Saddam Hussein's army invaded Kuwait and consequently the United Nations imposed economic sanctions on Iraq. In 1991, an international military alliance expelled the Iraqi army from Kuwait during a short war. Nevertheless, the economic sanctions remained in place—their removal required that Iraq should destroy its weapons of mass destruction. Subsequent years saw reports of acute suffering in Iraq. The sanctions undoubtedly greatly reduced the country's ability to import supplies of food and medicine. Particular concerns arose about the state of young children. These concerns crystalised in 1999 when, with cooperation from the Iraqi government, Unicef conducted a major demographic survey. The results of the survey indicated that the under-5 death rate in Iraq had increased hugely between 1990 and 1991 and had then continued at a very high level. The survey results were used both to challenge and support the case for the invasion of Iraq in 2003. And they were cited by Tony Blair in 2010 in his testimony to the Iraq Inquiry established by the British government. Indeed, the results of the 1999 Unicef/Government of Iraq survey are still cited. Since 2003, however, several more surveys dealing with child mortality have been undertaken. Their results show no sign of a huge and enduring rise in the under-5 death rate starting in 1991. It is therefore clear that Saddam Hussein's government successfully manipulated the 1999 survey in order to convey a very false impression—something that is surely deserving of greater recognition.